2021
DOI: 10.1002/pan3.10279
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the impact of avian diversity on attentional benefits and enjoyment of people experiencing urban green‐space

Abstract: 1. Biodiversity may play a key role in generating the well-being benefits of visiting green-spaces.2. The ability of people to accurately perceive variation in biodiversity is, however, unclear and evidence supporting links between biodiversity exposure and wellbeing outcomes remains equivocal. In part, this is due to the paucity of controlled experimental studies that deal adequately with confounding factors that covary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…Factors such as species diversity, community composition, and functional traits have been shown to influence human–bird interactions (e.g., Ainsworth et al, 2018; Clergeau et al, 2001; Clucas et al, 2011). Biodiversity and community composition—particularly native and specialist species—have been associated with positive attitudes (Dayer et al, 2016; Lerman & Warren, 2011; Warren et al, 2019) and greater enjoyment of green space (Douglas & Evans, 2021), which may, in turn, influence management practices. In one study, citizen scientists favored the removal of House Sparrow ( Passer domesticus) from nest boxes when they negatively perceived the species as outcompeting native songbirds for nesting sites (Larson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as species diversity, community composition, and functional traits have been shown to influence human–bird interactions (e.g., Ainsworth et al, 2018; Clergeau et al, 2001; Clucas et al, 2011). Biodiversity and community composition—particularly native and specialist species—have been associated with positive attitudes (Dayer et al, 2016; Lerman & Warren, 2011; Warren et al, 2019) and greater enjoyment of green space (Douglas & Evans, 2021), which may, in turn, influence management practices. In one study, citizen scientists favored the removal of House Sparrow ( Passer domesticus) from nest boxes when they negatively perceived the species as outcompeting native songbirds for nesting sites (Larson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Forest landscape preferences [220][221][222], restorative environments [65,223,224] Views, spaces, and changes Distant, panoramic, and detail views; private nooks, group, and ceremonial spaces "An overlook or scenic view somewhere is nice, adding to the sensory experience" (2). "A clearing in the woods where people can sit on the ground for a tea ceremony is nice .…”
Section: Design and Constructionmentioning
confidence: 99%
“…Good water quality is, however, important for physical access, and direct contact, interaction with, and immersion in water can be a highly therapeutic experience [284][285][286]. Wildlife can have a positive effect on forest and landscape preference and restoration, and studies have looked directly at their presence in the landscape [220] and as an indirect component in the overall biodiversity of a site [66,223,287]. Of the former studies, the visual presence of animals and insects can be an important part of a nature experience, while, for birds, it is often their song that adds to the experience [288].…”
Section: Vegetation Water and Wildlifementioning
confidence: 99%
“…Beyond the multifold benefits of green spaces to humans and biodiversity, the effect of biodiversity levels on human health and well-being outcomes has also been explored. Although studies have found mixed results, there is some initial evidence of a positive relationship 19 – 21 . Nonetheless requirements for human use and wildlife support may differ and a green space might not fulfill the demands for both dimensions at the same time.…”
Section: Introductionmentioning
confidence: 99%